Electrolyzed water catalyst and preparation method thereof

By loading RU and Ni on Zro2 and covering IRO2 on its surface to form IRO2@RU-NI/ZRO2 catalyst, the problem of poor stability of the RU base catalyst has improved the stability and activity of the catalyst, reducing the reducing the stability and activity of the catalyst, reducing it Cost promotes the development of PEM hydrogen -making systems.

CN119372699APending Publication Date: 2025-01-28WUXI WEIFU ENVIRONMENT PROTECTION CATALYST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411483220.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemistry, and particularly relates to an electrolyzed water catalyst and a preparation method thereof. The water electrolysis catalyst comprises a ZrO2 matrix, the matrix is loaded with Ru, Ni and Ir ternary metals, and the mass ratio of Ru to Ni to Ir is (3-8): (2-4): (2-7). Ru and Ni are supported on ZrO2, Ru-Ni / ZrO2 catalytic powder is formed through an alloying process, then the surface of the Ru-Ni / ZrO2 catalytic powder is coated with IrO2 through a colloid method process, firstly, Ru-Ni alloying causes remarkable tensile strain, a Ru-Ni bond has high structural stability and corrosion resistance, the stability of Ru is improved, and meanwhile the catalytic activity is also improved; secondly, the IrO2 at Ru-Ni / ZrO2 catalyst with the core-shell structure not only improves the stability of the catalyst to a certain extent, but also facilitates the improvement of the activity of the catalyst; and finally, Ru and Ni are used in a large proportion, so that the use cost of an electrolyzed water catalyst is reduced, and the cost of a PEM hydrogen production system is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a water electrolysis catalyst and a preparation method thereof. Background Art

[0002] Hydrogen is known as the most promising energy carrier in the 21st century. Using renewable energy such as solar energy and wind energy, electrolysis of water to produce hydrogen is a relatively effective hydrogen production technology.

[0003] In principle, the construction of a PEM water electrolyzer is similar to that of a PEM fuel cell, but they operate differently. During operation of a PEM fuel cell, oxygen is reduced at the cathode of the fuel cell and hydrogen is oxidized at the anode, in which case water is produced and an electric current is generated.

[0004] In PEM hydrolysis, the current and the electrodes are opposite and the decomposition of water occurs. Oxygen is released at the anode ("OER" for short - oxygen evolution reaction), while the reduction of protons occurs at the cathode ("HER" for short - hydrogen evolution reaction), in which the protons migrate through the polymer electrolyte membrane. Thus, water is decomposed into hydrogen and oxygen with the aid of an electric current.

[0005] A PEM water electrolysis device generally comprises a polymer electrolyte membrane (eg Nafion from Dupont) sandwiched between a pair of electrode layers and a pair of porous current collectors (or gas diffusion layers) mounted on both sides of the electrode layers, respectively.

[0006] In a PEM water electrolysis device, a platinum / carbon catalyst is used as an anode electrocatalyst (for the oxidation of hydrogen) and a cathode electrocatalyst (for the reduction of oxygen). In a PEM water electrolysis device, carbon-based materials such as platinum / carbon catalysts and carbon fiber-based gas diffusion layers cannot be used on the anode side because the carbon is corroded by the oxygen released during the water electrolysis process.

[0007] Among all the precious metals, platinum is the most active catalyst for the hydrogen release reaction (HER) on the cathode and can be used at medium loadings. As for the oxygen release process, the unique electrocatalytic properties of iridium and iridium oxide are well known. Therefore, for the oxygen release reaction (HER) on the anode side, a higher proportion of metallic iridium is beneficial, but the high price and low output of Ir are not conducive to the further development of PEM hydrogen production systems; the performance cost of Ru-based catalysts is better than that of Ir-based catalysts, but the stability is slightly worse. How to improve the stability of Ru-based catalysts has become a top priority. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a water electrolysis catalyst and a preparation method thereof. The present invention supports Ru and Ni on ZrO2, forms Ru-Ni / ZrO2 catalytic powder by alloying process, and then coats IrO2 on the surface of Ru-Ni / ZrO2 catalytic powder by colloid process. Firstly, the alloying of Ru-Ni causes significant tensile strain, and the Ru-Ni bond has strong structural stability and corrosion resistance, which improves the stability of the Ru base and also improves the catalytic activity; secondly, the core-shell structure of the IrO2@Ru-Ni / ZrO2 catalyst not only improves the stability of the catalyst to a certain extent, but also helps to improve the catalyst activity; finally, the large proportion of Ru and Ni reduces the use cost of the water electrolysis catalyst, which is conducive to reducing the cost of the PEM hydrogen production system.

[0009] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:

[0010] In a first aspect, an embodiment of the present invention provides a water electrolysis catalyst, which includes a substrate, the substrate is ZrO2, and the substrate is loaded with ternary metals Ru, Ni and Ir, and the mass ratio of Ru:Ni:Ir is 3-8:2-4:2-7.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing the water electrolysis catalyst according to the first aspect, comprising the following steps:

[0012] Preparation of Ru-Ni / ZrO2 Materials

[0013] (1) Weighing materials: Weigh ruthenium nitrate, nickel nitrate and ZrO2 respectively according to the weight ratio of the solidified material of 2-3:1-2:3-5;

[0014] (2) Determination of water absorption of ZrO2: The water absorption of ZrO2 was determined by the incipient wetness impregnation process;

[0015] (3) Preparation of bimetallic Ru and Ni solution: Add the ruthenium nitrate and nickel nitrate in step (1) into polyethylene glycol, the mass of which is 2-3 times the total mass of the ruthenium nitrate and nickel nitrate, stir for 0.5-1h, and add a corresponding mass of water according to the water absorption rate of ZrO2 in step (2);

[0016] (4) Loading of Ru and Ni: The solution containing ruthenium nitrate and nickel nitrate in step (3) is loaded on ZrO2 by an incipient wetness impregnation process, and then dried and calcined;

[0017] (5) High temperature alloying: alloying the material obtained in step (4) at high temperature in a H2-Ar mixed atmosphere at a temperature of 700-800°C for 1-2 hours to obtain Ru-Ni / ZrO2;

[0018] Preparation of IrO2@Ru-Ni / ZrO2 Materials

[0019] (6) Weighing materials: weigh H2IrCl6 and Ru-Ni / ZrO2 respectively according to the solidified material mass ratio of 1-2:8-9;

[0020] (7) Formation of colloidal Ir complex: Add the H2IrCl6 weighed in step (6) to deionized water, heat to 80°C, first adjust the pH to 12-13 with alkali, then adjust the pH of the solution to 8, and stir for 2-5h;

[0021] (8) Surface loading of Ir: Add the Ru-Ni / ZrO2 prepared in step (6) to the solution prepared in step (7) and stir for 4-5 h;

[0022] (9) Filtration and washing: The slurry in step (8) is filtered and washed to remove the Cl - And Na + ions, retaining the solid portion;

[0023] (10) Catalyst drying: drying the solid part in step (8);

[0024] (11) Catalyst calcination: The dried catalyst is placed in a muffle furnace for calcination, and after heat preservation, it is cooled to room temperature to obtain a water electrolysis catalyst.

[0025] Furthermore, the cleaning solvent in step (9) is deionized water, and the number of cleaning times is 3-5 times.

[0026] Furthermore, the drying temperature of steps (4) and (10) is 80-90° C., and the drying time is 8-12 h.

[0027] Furthermore, the calcination temperature of steps (4) and (11) is 450-600° C., and the calcination time is 1-6 h.

[0028] The technical solution provided by the embodiment of the present invention has the following beneficial effects:

[0029] (1) The electrolytic water catalyst of the present invention is a process improvement over the existing Ir-based catalyst. After the improvement, the utilization rate of the three metals Ru, Ni and Ir is higher, and the catalytic activity is further improved.

[0030] (2) The electrolytic water catalyst of the present invention uses ZrO2 as a loading matrix and utilizes the synergistic effect of Zr and the precious metals Ru and Ir to promote the dispersion of the precious metals on the surface of ZrO2. It is also beneficial to the formation of a certain proportion of metallic Ru and Ir, thereby improving the activity of the catalyst.

[0031] (3) The water electrolysis catalyst of the present invention forms Ru-Ni through an alloying process, which improves the structural stability and corrosion resistance of Ru, thereby improving the electrochemical activity and durability.

[0032] (4) The electrolytic water catalyst of the present invention forms a core-shell IrO2@Ru-Ni / ZrO2 through a certain process, which promotes the dispersion of Ir on the surface, and to a certain extent not only improves the catalyst activity but also helps to improve the catalyst stability.

[0033] (5) The water electrolysis catalyst of the present invention reduces the proportion of Ir and reduces the catalyst cost. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0035] Example 1

[0036] A method for preparing a water electrolysis catalyst comprises the following steps:

[0037] Preparation of Ru-Ni / ZrO2 Materials

[0038] (1) Weighing materials: Weigh ruthenium nitrate, nickel nitrate and ZrO2 respectively according to the weight ratio of the solidified material of 3:1:5;

[0039] (2) Determination of water absorption of ZrO2: The water absorption of ZrO2 was determined by the incipient wetness impregnation process;

[0040] (3) Preparation of bimetallic Ru and Ni solutions: Add the ruthenium nitrate and nickel nitrate in step (1) into polyethylene glycol 400, the mass of which is twice the total mass of the ruthenium nitrate and nickel nitrate, add a corresponding mass of water according to the water absorption rate of ZrO2 in step (2), and stir for 1 hour;

[0041] (4) Loading of Ru and Ni: The solution containing ruthenium nitrate and nickel nitrate in step (3) is loaded on ZrO2 by incipient wetness impregnation process, dried and calcined at a drying temperature of 80°C for 12 h and a calcination temperature of 500°C for 2 h;

[0042] (5) High temperature alloying: the material obtained in step (4) is alloyed at high temperature in a H2-Ar mixed atmosphere (the volume content of H2 is 5%), the alloying temperature is 700°C, the time is 2h, and Ru-Ni / ZrO2 is obtained;

[0043] Preparation of IrO2@Ru-Ni / ZrO2 Materials

[0044] (6) Weighing materials: weigh H2IrCl6 and Ru-Ni / ZrO2 respectively according to the solidified material mass ratio of 2:8;

[0045] (7) Formation of colloidal Ir complex: Add the H2IrCl6 weighed in step (6) to deionized water, heat to 80°C, adjust the pH to 12 with alkali, then adjust the pH of the solution to 8 with 0.1M HNO3, and stir for 5 h;

[0046] (8) Surface loading of Ir: Add the Ru-Ni / ZrO2 weighed in step (6) to the solution in step (7) and stir for 4 h;

[0047] (9) Filtration and washing: The slurry in step (8) is filtered and the solid is washed 3-5 times with deionized water to remove the Cl - And Na + ions, retaining the solid portion;

[0048] (10) Catalyst drying: The solid part in step (8) was dried at a temperature of 80° C. for 12 h;

[0049] (11) Catalyst calcination: The dried catalyst was placed in a muffle furnace for calcination at a temperature of 500°C for 2 h. After the heat preservation, it was cooled to room temperature to obtain a water electrolysis catalyst.

[0050] Example 2

[0051] A method for preparing a water electrolysis catalyst comprises the following steps:

[0052] Preparation of Ru-Ni / ZrO2 Materials

[0053] (1) Weighing materials: Weigh ruthenium nitrate, nickel nitrate and ZrO2 respectively according to the weight ratio of the solidified material of 3:2:4;

[0054] (2) Determination of water absorption of ZrO2: The water absorption of ZrO2 was determined by the incipient wetness impregnation process;

[0055] (3) Preparation of bimetallic Ru and Ni solutions: Add the ruthenium nitrate and nickel nitrate in step (1) into polyethylene glycol 400, the mass of which is 2.5 times the total mass of the ruthenium nitrate and nickel nitrate, add a corresponding mass of water according to the water absorption rate of ZrO2 in step (2), and stir for 1 hour;

[0056] (4) Loading of Ru and Ni: The solution containing ruthenium nitrate and nickel nitrate in step (3) is loaded on ZrO2 by an incipient wetness impregnation process, and then dried and calcined at a drying temperature of 85°C for 12 hours and a calcination temperature of 550°C for 2 hours.

[0057] (5) High temperature alloying: the material in step (4) is alloyed at high temperature in a H2-Ar mixed atmosphere (the volume content of H2 is 5%), the alloying temperature is 800°C, the time is 2h, and Ru-Ni / ZrO2 is obtained;

[0058] Preparation of IrO2@Ru-Ni / ZrO2 Materials

[0059] (6) Weighing of materials: Weigh H2IrCl6 and Ru-Ni / ZrO2 respectively at a solidified material mass ratio of 2:9;

[0060] (7) Formation of colloidal Ir complex: Add the H2IrCl6 weighed in step (6) to deionized water, heat to 80°C, adjust the pH to 12.5 with alkali, then adjust the pH of the solution to 8 with 0.1M HNO3, and stir for 5 h;

[0061] (8) Surface loading of Ir: Add the Ru-Ni / ZrO2 weighed in step (6) to the solution in step (7) and stir for 4 h;

[0062] (9) Filtration and washing: The slurry in step (8) is filtered and the solid is washed 3-5 times with deionized water to remove the Cl - And Na + ions, retaining the solid portion;

[0063] (10) Catalyst drying: drying the solid part in step (8) at a drying temperature of 85° C. for 12 h;

[0064] (11) Catalyst calcination: The dried catalyst was placed in a muffle furnace for calcination at a temperature of 550° C. for 2 h. After the heat preservation, it was cooled to room temperature to obtain a water electrolysis catalyst.

[0065] Example 3

[0066] A method for preparing a water electrolysis catalyst comprises the following steps:

[0067] Preparation of Ru-Ni / ZrO2 Materials

[0068] (1) Weighing materials: Weigh ruthenium nitrate, nickel nitrate and ZrO2 respectively according to the weight ratio of the solidified material of 2:1:4;

[0069] (2) Determination of water absorption of ZrO2: The water absorption of ZrO2 was determined by the incipient wetness impregnation process;

[0070] (3) Preparation of bimetallic Ru and Ni solutions: Add the ruthenium nitrate and nickel nitrate in step (1) into polyethylene glycol 400, the mass of which is 3 times the total mass of the ruthenium nitrate and nickel nitrate, add a corresponding mass of water according to the water absorption rate of ZrO2 in step (2), and stir for 1 hour;

[0071] (4) Loading of Ru and Ni: The solution containing ruthenium nitrate and nickel nitrate in step (3) is loaded on ZrO2 by an incipient wetness impregnation process, and then dried and calcined at a drying temperature of 90°C for 12 h and a calcination temperature of 600°C for 2 h.

[0072] (5) High temperature alloying: the material in step (4) is alloyed at high temperature in a H2-Ar mixed atmosphere (the volume content of H2 is 5%), the alloying temperature is 750°C, the time is 2h, and Ru-Ni / ZrO2 is obtained;

[0073] Preparation of IrO2@Ru-Ni / ZrO2 Materials

[0074] (6) Weighing materials: Weigh H2IrCl6 and Ru-Ni / ZrO2 respectively at a solidified material mass ratio of 1:9;

[0075] (7) Formation of colloidal Ir complex: deionized water was added to the H2IrCl6 weighed in step (6), heated to 80°C, the pH was first adjusted to 13 with alkali, and then the pH of the solution was adjusted to 8 with 0.1 M HNO3, and stirred for 5 h;

[0076] (8) Surface loading of Ir: Add the Ru-Ni / ZrO2 weighed in step (6) to the solution in step (7) and stir for 4 h;

[0077] (9) Filtration and washing: The slurry in step (8) is filtered and the solid is washed 3-5 times with deionized water to remove the Cl - And Na + ions, retaining the solid portion;

[0078] (10) Catalyst drying: drying the solid part in step (8) at a drying temperature of 90° C. for 12 h;

[0079] (11) Catalyst calcination: The dried catalyst was placed in a muffle furnace for calcination at a temperature of 600°C for 2 h. After the heat preservation, it was cooled to room temperature to obtain a water electrolysis catalyst.

[0080] Comparative Example 1

[0081] A method for preparing a water electrolysis catalyst comprises the following steps:

[0082] (1) Weighing materials: weigh H2IrCl6 and RuCl3 hydrate in a molar ratio of 1:2 respectively;

[0083] (2) Adding bimetallic Ir and Ru: Add the IrCl3 hydrate and RuCl3 hydrate prepared in step (1) into deionized water respectively and stir for 1 h;

[0084] (3)Ir + 、Ru + Hydroxylation complexation: adjust the pH of the solution in step (2) to 12 with 0.1 M NaOH and stir for 4 h;

[0085] (4) pH adjustment: adjust the solution pH to 8 with 0.1 M HNO3 and stir for 2 h;

[0086] (5) Filtration and cleaning: The slurry in step (4) is filtered, separated, and cleaned to remove the Cl - And Na + ions, washed 5 times with deionized water, and the solid part was retained;

[0087] (6) Catalyst drying: drying the solid part in step (5) at a drying temperature of 90° C. for 12 h;

[0088] (7) Catalyst Calcination: The dried catalyst was placed in a muffle furnace and calcined at 500°C for 1 h. After the heat preservation, it was cooled to room temperature and the catalyst was weighed.

[0089] The catalytic activity of the catalysts prepared in Examples 1 to 3 and Comparative Example 1 was evaluated.

[0090] Catalyst activity evaluation conditions: Preparation of electrodes, catalyst-coated membranes and membrane-electrode assemblies; preparation of IrO2@Ru-Ni / ZrO2 catalyst into membrane electrode slurry by adding suitable solvent and ionomer Nafion material; dispersion of catalyst sample in alcohol-water solution containing 20% ​​Nafion; deposition of catalyst coating on proton exchange membrane by ultrasonic dispersion and spraying, and drying to remove solvent in catalyst coating; application of IrO2@Ru-Ni / ZrO2 to the anode side; loading of 0.5 mg / cm 2 On the cathode side, a standard Pt catalyst (e.g. Pt / C) was used; the cathode loading was 0.35 mg Pt / cm 2 By measuring the constant current of 1A / cm 2 The electrochemical properties of the catalyst material were determined by the onset potential of oxygen release.

[0091] Two parameters were used to determine the electrochemical activity: operating voltage at a constant current. The test results are shown in Table 1.

[0092] Table 1 Activity evaluation results of catalysts obtained in Examples 1-3 and Comparative Example 1

[0093] Test Category Comparative Example 1 Example 1 Example 2 Example 3 Oxygen release operating voltage (V) 1.73 1.52 1.54 1.50

[0094] According to the evaluation results of catalyst activity in Table 1, it can be seen that Examples 1, 2, and 3 have a constant current of 1 A / cm 2 Under the condition of low operating voltage, it means that the catalyst prepared by the present invention has high catalytic activity, so that the production of unit volume of hydrogen has low specific energy consumption, and therefore, has high hydrogen production rate under given electrolytic cell voltage.

[0095] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A water electrolysis catalyst, characterized in that The water electrolysis catalyst comprises a substrate, which is ZrO2, and the substrate is loaded with ternary metals of Ru, Ni and Ir, and the mass ratio of Ru:Ni:Ir is 3-8:2-4:2-7.

2. The method for preparing the water electrolysis catalyst according to claim 1, characterized in that: The following steps are involved: Preparation of Ru-Ni / ZrO2 Materials (1) Weighing of materials: Weigh ruthenium nitrate, nickel nitrate and ZrO2 respectively according to the weight ratio of the solidified material of 2-3:1-2:3-5; (2) Determination of water absorption of ZrO2: The water absorption of ZrO2 was determined by the initial wetness impregnation process; (3) Preparation of bimetallic Ru and Ni solutions: Add the ruthenium nitrate and nickel nitrate in step (1) into polyethylene glycol, the mass of which is 2-3 times the total mass of the ruthenium nitrate and nickel nitrate, stir for 0.5-1h, and add a corresponding mass of water according to the water absorption rate of ZrO2 in step (2); (4) Loading of Ru and Ni: The solution containing ruthenium nitrate and nickel nitrate in step (3) is loaded on ZrO2 by an incipient wetness impregnation process, and then dried and calcined; (5) High temperature alloying: alloying the material obtained in step (4) in a H2-Ar mixed atmosphere at a high temperature of 700-800°C for 1-2 hours to obtain Ru-Ni / ZrO2; Preparation of IrO2@Ru-Ni / ZrO2 Materials (6) Weighing of materials: Weigh H2IrCl6 and Ru-Ni / ZrO2 respectively according to the solidified material mass ratio of 1-2:8-9; (7) Formation of colloidal Ir complex: Add the H2IrCl6 weighed in step (6) to deionized water, heat to 80°C, first adjust the pH to 12-13 with alkali, then adjust the pH of the solution to 8, and stir for 2-5 hours; (8) Surface loading of Ir: Add the Ru-Ni / ZrO2 prepared in step (6) to the solution prepared in step (7) and stir for 4-5 h; (9) Filtration and washing: Filter and wash the slurry in step (8) to remove the Cl - And Na + ions, retaining the solid portion; (10) Catalyst drying: drying the solid part in step (8); (11) Catalyst calcination: The dried catalyst is placed in a muffle furnace for calcination. After the heat preservation is completed, the catalyst is cooled to room temperature to obtain a water electrolysis catalyst.

3. The method for preparing the water electrolysis catalyst according to claim 2, characterized in that: The cleaning solvent in step (9) is deionized water, and the number of cleaning times is 3-5 times.

4. The method for preparing the water electrolysis catalyst according to claim 2, characterized in that: The drying temperature of steps (4) and (10) is 80-90°C and the drying time is 8-12h.

5. The method for preparing a water electrolysis catalyst according to claim 2, characterized in that: The calcination temperature of steps (4) and (11) is 450-600°C, and the calcination time is 1-6h.

Citation Information

Cited By

  • Electrolytic water catalyst under intermittent fluctuation working condition and preparation method and application thereof

    CN122669421A